Energy Management in Wireless Cellular and Ad-hoc Networks - Shakir, Muhammad Zeeshan; Imran, Muhammad Ali.; Qaraqe, Khalid A.; Alouini, Mohamed-Slim.; Vasilakos, Athanasios V.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book investigates energy management approaches for energy efficient or energy-centric system design and architecture and presents end-to-end energy management in the recent heterogeneous-type wireless network medium. It also considers energy management in wireless sensor and mesh networks by exploiting energy efficient transmission techniques and protocols. and explores energy management in emerging applications, services and engineering to be facilitated with 5G networks such as WBANs, VANETS and Cognitive networks. A special focus of the book is on the examination of the energy management practices in emerging wireless cellular and ad hoc networks. Considering the broad scope of energy management in wireless cellular and ad hoc networks, this book is organized into six sections covering range of Energy efficient systems and architectures; Energy efficient transmission and techniques; Energy efficient applications and services. .
Energy Management in Heterogeneous Networks -- Energy Management and Energy Efficiency in Cellular Systems -- Energy Management in Ad Hoc Networks -- Energy Management in Cognitive Radio Networks -- Energy Management in Emerging Wireless Networks -- Energy Management Practices in Wireless Networks.
Keywords: Telecommunication; Energy policy; Energy and state; Communications Engineering, Networks; Energy Policy, Economics and Management